5-HT2A Gene Variants Moderate the Association between PTSD and Reduced Default Mode Network Connectivity - Miller, Mark W.; Sperbeck, Emily; Robinson, Meghan E.; Sadeh, Naomi; Wolf, Erika J.; Hayes, Jasmeet P.; Logue, Mark; Schichman, Steven A.; Stone, Angie; Milberg, William; McGlinchey, Regina (Frontiers in Neuroscience, 2016)
The default mode network (DMN) has been used to study disruptions of functional connectivity in a wide variety of psychiatric and neurological conditions, including posttraumatic stress disorder (PTSD). Studies indicate that the serotonin system exerts a modulatory influence on DMN connectivity; however, no prior study has examined associations between serotonin receptor gene variants and DMN connectivity in either clinical or healthy samples. We examined serotonin receptor single nucleotide polymorphisms (SNPs), PTSD, and their interactions for association with DMN connectivity in 134 White non-Hispanic veterans. We began by analyzing candidate SNPs identified in prior meta-analyses of relevant psychiatric traits and found that rs7997012 (an HTR2A SNP), implicated previously in anti-depressant medication response in the Sequenced Treatment Alternatives for Depression study (STAR*D; 1), interacted with PTSD to predict reduced connectivity between the posterior cingulate cortex (PCC) and the right medial prefrontal cortex and right middle temporal gyrus (MTG). rs130058 (HTR1B) was associated with connectivity between the PCC and right angular gyrus. We then expanded our analysis to 99 HTR1B and HTR2A SNPs and found two HTR2A SNPs (rs977003 and rs7322347) that significantly moderated the association between PTSD severity and the PCC-right MTG component of the DMN after correcting for multiple testing. Finally, to obtain a more precise localization of the most significant SNP x PTSD interaction, we performed a whole cortex vertex-wise analysis of the rs977003 effect. This analysis revealed the locus of the pre-frontal effect to be in portions of the superior frontal gyrus, while the temporal lobe effect was centered in the middle and inferior temporal gyri. These findings point to the influence of HTR2A variants on DMN connectivity and advance knowledge of the role of 5-HT2A receptors in the neurobiology of PTSD.